THE EFFECT OF VARIATION CONCENTRATION AND DEPOSITION PARAMETER TO THE OPTICAL CHARACTERISTICS AND THE CRYSTALLITE PROPERTIES OF ZINC OXIDE - Waode Sukmawati Arsyad; Ulpiani Ulpiani; Muh. Angga Anugerah; La Aba; Ida Usman (Program Studi Fisika Universitas Negeri Jakarta, 2022)
The objective of the study was to obtain the ZnO thin films with variation concentration of zinc acetate dehydrate (ZAD), and variation of spin coater speed and rotation time. We observed the effect of the former parameters on the optical characteristics that comprised of the spectrum of absorption, transmittance, and ZnO crystallite size from UV-Vis spectrometer and XRD orderly. For the analysis of the effect of the variation of concentration, ZAD diluted into ethanol with the concentration 0.1M, 0.25M, 0.5M, 0.75M and 1M, with the addition of diethanolamine (DEA). Then it was deposited on the glass substrate with spin coater, continued by the heating on the hotplate with the number of layer's variation. For the analysis of deposition parameter effect on the transmittance and the size of ZnO crystal, we used 0.25M ZnO precursor solution with the addition of DEA, then deposited by speed and time of rotation of spin coater of 1230 rpm, 2500 rpm, and 3200 rpm for 10, 15 and 30 seconds of each. The smallest absorbance value 0.05 obtained for single layer 0.1M ZnO, while the maximum transmittance value obtained for three-layer 0.25M ZnO. Concentration variation did not affect the energy gap, whose value was approximately 3.2 eV for all samples. From the XRD result, we found that deposition time affected the number of diffraction lines, the size of the crystallite, and the transmittance.